STRUKTUR KOMUNITAS DAN ZONASI VEGETASI MANGROVE DESA DARUNU KECAMATAN WORI KABUPATEN MINAHASA UTARA - Udin Upara; Janny Dirk Kusen; Calvyn F.A. Sondak; Joshian N.W Schaduw; Sandra Olivia Tilaar; Ridwan Lasabuda (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Mangrove ecosystem is a collection of distinctive plant types that contained in tropical and subtropical coastal region. The purpose of research was to find out the community structure and mangrove zonation at Darunu Village, Wori District, North Minahasa Regency. The research was conducted by   the quadrant transect line method. It was done by pulling a straight line, perpendicular from the outermost mangrove area to the land direction, along 100 m by determining three data retrieval Station. To determine the condition of mangrove then density, species frequency, species coverage, important value index, diversity index and equality types were analyzed. The result found 5 mangroves species, namely: Rhizophora apiculata, R. mucronata, Sonneratia alba, Bruguiera gymnorrhiza and Avicennia officinalis. The highest density value was R.apiculata, as well as species frequency, while the species coverage value  found in S. alba. The diversity value found at Station 2. The zonation of mangrove vegetation in Darunu village respectively, at Station 1 and 2 in the front was overgrown by R.apiculata species with sandy mud substrate.  The Station 3 was overgrown by S.alba species with sandy mud. Generalyl, this location substrate contains of sandy mud and mud.Keywords : Mangrove, community structure, zonation.